Chemical Fingerprint and Metabolic Fingerprint Analysis of the Medicinal Extract of Corydalis yanhusuo by HPLC-UV and HPLC-MS Methods - Li, Kaitong; Xing, Dongming; Jin, Wen; Sun, Hong; Shi, Yue (Asian Journal of Chemistry, 2010)
HPLC-UV and HPLC-MS techniques were used in fingerprint analysis of the medicinal extract of Corydalis yanhusuo. An HPLC profile of medicinal extract of Corydalis yanhusuo was established as a characteristic fingerprint and employed to assess the consistency and differences between extracts. To determine the major constituents of medicinal extract of Corydalis yanhusuo for quality control, 12 major chromatographic peaks were characterized. To explore the in vivo metabolism of the major active constituents' rat plasma was analyzed by HPLC-MS following oral administration of medicinal extract of Corydalis yanhusuo at different time intervals. These results indicate that the quaternary alkaloids are significant for the biological activity of medicinal extract of Corydalis yanhusuo. It is concluded that the chemical fingerprint combined with the metabolic fingerprint is a useful means of controlling the quality of medicinal extract of Corydalis yanhusuo and clarifying the possible mechanism of action.